Thermal stability and performances of hybrid nanoparticles for convective heat transfer phenomenon with multiple solutions. (December 2021) - Kolsi, Lioua; Dero, Sumera; Lund, Liaquat Ali; Alqsair, Umar F.; Omri, Mohamed; Khan, Sami Ullah
Abstract: The thermal reliability of hybrid nanoparticles is quite impressive which presents many dynamic applications in solar systems, extrusion processes, thermal devices, cooling systems, and many engineering processes. This paper explores the flow of three-dimensional (3D), steady, magnetohydrodynamic of alumina and copper/water hybrid nanofluid over the nonlinear shrinking/stretching surface. A mathematical model was developed by adopting the model of Tiwari and Das in the form of partial differential equations (PDEs), which were then transferred into an analogous set of non-linear ordinary differential equations (ODEs) by employing nonlinear similarity variables. The resulting ODEs were solved by employing abvp4csolver numerically in the MATLAB package. For validation, the collected empirical outcomes were numerically correlated with those of the preceding studies and were in strong alignment. It has been demonstrated that dual branches occur within the different ranges of magnetic, suction, and shrinking/stretching parameters. Dual (no) branches have been discovered when b ≤ b c i ( b > b c i ) and M ≥ M c i ( M < M c i ) where i = 1, 2, 3 . Because of the non-uniqueness of the branches, a stability analysis was performed, and it was discovered that the upper branch was stable. Further, velocity in y -direction and temperature of hybrid nanofluid increase in both branches when the volume fraction of φ C u increases.